(untitled) (Research, Society and Development, 2021)
Objectives: To analyze the symptoms of active and sedentary climacteric women. Methods: The cross-sectional research was carried out with 60 climacteric women, where they were divided into three groups: 20 who played aerobic exercise, 20 performed anaerobic and 20 sedentary. Data collection was performed using two questionnaires related to sociodemographic characteristics and the Menopause Rating Scale (MRS). For data analysis, the Pearson Chi-square test was used with a 95% confidence interval and significance set at p <0.05. Results: The average age of the groups was 49.25 ± 0.97 years to 52.95 ± 1.37 years. The results point to a significant difference for the groups who practice physical exercises with a decline in climacteric symptoms. Conclusion: The study showed that women, who exercised anaerobic exercises accompanied by a professional, obtained a better result in the decrease of climacteric symptoms and a better quality of life.